2011
DOI: 10.1001/archsurg.2011.197
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome for Anal Fistula Surgery

Abstract: Setting: A regional tertiary referral center.Patients: Adult patients with anal fistula secondary to cryptoglandular disease.Interventions: Fistulotomy, advancement flap, and fistula plugging.Main Outcome Measures: Rates of operative failure (persistent fistula), incontinence, and septic complications. We evaluated age, sex, previous operation, fistula type, number of fistula tracts, horseshoe fistula, and intervention type to determine their independent influence on outcomes.Results: One hundred seventy-nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 31 publications
(43 reference statements)
3
55
2
3
Order By: Relevance
“…Mizrahi et al found an increased risk in the presence of prior attempts at repair [ 10 ]. Abbas et al found an increased risk of incontinence with older age and high transsphincteric fi stulas, but the majority of the patients in this study had fi stulotomies, with only 10.6 % of patients having advancement fl aps [ 13 ]. Although there is little data with which to counsel patients, the patients at higher risk for incontinence after advancement fl ap are likely those who are at higher risk with any procedure-those with baseline disturbances in continence, prior repairs, women, and older individuals.…”
Section: Risk Factors For Incontinencecontrasting
confidence: 62%
See 3 more Smart Citations
“…Mizrahi et al found an increased risk in the presence of prior attempts at repair [ 10 ]. Abbas et al found an increased risk of incontinence with older age and high transsphincteric fi stulas, but the majority of the patients in this study had fi stulotomies, with only 10.6 % of patients having advancement fl aps [ 13 ]. Although there is little data with which to counsel patients, the patients at higher risk for incontinence after advancement fl ap are likely those who are at higher risk with any procedure-those with baseline disturbances in continence, prior repairs, women, and older individuals.…”
Section: Risk Factors For Incontinencecontrasting
confidence: 62%
“…A higher recurrence rate has been found with fl ap as compared to fi stulotomy [ 25 , 48 , 51 ], although one study found no difference in recurrence rate [ 13 ]. However, the problem with comparing these two methods, as acknowledged by many of the authors of these studies, is that endorectal advancement fl ap is generally used in situations where a fi stulotomy would be associated with an unacceptably high risk of incontinence, either due to the high location of the fi stula or due to preexisting impaired continence.…”
Section: Fistulotomymentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 If this is performed in patients with high fistulas, there is a real risk of fecal incontinence. 3,4 In such a situation, it is not infrequent that a seton would be inserted to ensure continual drainage of any sepsis before any subsequent definitive intervention.…”
mentioning
confidence: 99%